Dataset: Multi-view video sequences of Megathyrsus maximus and Urochloa spp. in field conditions for 3D reconstruction and temporal phenotyping - Ruiz-Hurtado, Andres Felipe; Madera Doria, Pascual; Mayorga Cobos, Mildred Julieth; Madera Doria, Yaira Yulieth; Escobar Graciano, Miller; Cardoso Arango, Juan Andres (2025)
This dataset contains a time-series collection of 135 high definition video sequences of tropical forage grasses (Megathyrsus maximus and Urochloa spp.) grown under open field conditions. The study follows various genotypes with 3 replications each, captured over a growing period. Week 1 (Pre-Pruning): This sequence represents the full biomass before the pruning event. Weeks 2–9 (Regrowth): This sequence represents the regrowth period. The dataset is intended as a primary source for 3D reconstruction using Neural Radiance Fields (NeRF) and 3D Gaussian Splatting (3DGS).